TRANSFORMASI PEMBELAJARAN ILMU FALAK dI ERA INDUSTRI (Application and Inspiring Learning Methods) - Mursyid Fikri dan Baharuddin (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2021)
Abstrac The industry has experienced a very rapid revolution phase, namely industry 4.0, this has consequences for science and sharia education to be able to prepare individuals who have competence in facing various challenges in the future by applying or producing a work that is a symbol of scientific dialectics. This research is a library research using a descriptive qualitative method approach that connects the existing theory with the descriptive reality of astronomy today. Astrology is the most important part in the history of Islamic civilization. History has recorded that scholars and Al-Falaky (a title for astronomy activists) emerged when Islamic civilization was at its golden peak and when Islam experienced a decline, the echo of astronomy was no longer heard, even today many Muslims do not know the term